1880 Ga. Laws 151, in 1914 Ga. Code Ann. 236 - (:unkn) unknown (My University, 1880)
§ 349 (§343): Prohibited pointing a gun or pistol, loaded or unloaded, at another. Violators guilty of a misdemeanor.
Keywords: BRANDISHING